(untitled) (RuMoRes, 2015)
This article wants to observe how the car racing posters, notably those drawn by French artist Géo Ham, can engender, in his poetic image of the automobile, a kind of static image that mentions the almost cinematic form of movement, called here moving-crystal. Using the theoretical framework of Gilles Deleuze and Groupe μ, the goal here is to see how these posters’ mise en scènes are portemanteau constructions that unite in a imagetic representation both movement-image as the time-image and, most important, that portemanteau is the graphical representation of the movement-crystal and it is crucial to the poetic thought of imagery arts focused on racing and sports.